Resistenze agli impianti eolici nell’Appennino Settentrionale (1995 - 2012) (Resistances to wind farms in the Northern Apennines (1995 - 2012)) - Alessandro Mengozzi (Coordinamento SIBA, 2013)
Outcomes of democratization paths have been addressed within literature on democratic consolidation as well as on revolution. These approaches have however never been linked with social movement theory that, I argue in this article, can provide new lenses to explain how movements’ characteristics at the time of transition might have an impact on the quality of ensuing democracy. As the same time, looking at effects of social movements in terms of democratization can help broadening social movement studies, that have rarely addressed this type of effects. I am in particular interested in linking reflections (and empirical evidence) on effects of social movements to the typology on paths towards democratization that I have developed in other works. Looking especially at Central Eastern Europe post-1989, I single out the different characteristics of contentious politics in countries that underwent, respectively, eventful democratization, participated pacts and troubled democratization. Protest event analysis as constituted the empirical basis for the analysis